Immune evasion by proteolytic shedding of natural killer group 2, member D ligands in Helicobacter pylori infection - Margit Anthofer; Markus Windisch; Rosa Haller; Sandra Ehmann; Sebastian Wrighton; Michael Miller; Lorenz Schernthanner; Iris Kufferath; Silvia Schauer; Barbara Jelušić; Sabine Kienesberger; Sabine Kienesberger; et al. (Frontiers in Immunology, 2024)
BackgroundHelicobacter pylori (H. pylori) uses various strategies that attenuate mucosal immunity to ensure its persistence in the stomach. We recently found evidence that H. pylori might modulate the natural killer group 2, member 2 (NKG2D) system. The NKG2D receptor and its ligands are a major activation system of natural killer and cytotoxic T cells, which are important for mucosal immunity and tumor immunosurveillance. The NKG2D system allows recognition and elimination of infected and transformed cells, however viruses and cancers often subvert its activation. Here we aimed to identify a potential evasion of the NKG2D system in H. pylori infection.MethodsWe analyzed expression of NKG2D system genes in gastric tissues of H. pylori gastritis and gastric cancer patients, and performed cell-culture based infection experiments using H. pylori isogenic mutants and epithelial and NK cell lines.ResultsIn biopsies of H. pylori gastritis patients, NKG2D receptor expression was reduced while NKG2D ligands accumulated in the lamina propria, suggesting NKG2D evasion. In vitro, H. pylori induced the transcription and proteolytic shedding of NKG2D ligands in stomach epithelial cells, and these effects were associated with specific H. pylori virulence factors. The H. pylori-driven release of soluble NKG2D ligands reduced the immunogenic visibility of infected cells and attenuated the cytotoxic activity of effector immune cells, specifically the anti-tumor activity of NK cells.ConclusionH. pylori manipulates the NKG2D system. This so far unrecognized strategy of immune evasion by H. pylori could potentially facilitate chronic bacterial persistence and might also promote stomach cancer development by allowing transformed cells to escape immune recognition and grow unimpeded to overt malignancy.